Avaliação da expressão gênica de citocinas em resposta à infecção experimental por fusobacterium nucleatum e enterococcus faecalis. - Andressa Lamari Silva Pereira (2011)
The aim of this study was evaluate the gene expression of proinflammatory (RANKL, TNF- e IFN-) and regulatory (TGF- e IL-10) cytokines in response to experimental infection in Balb/c mice molars by microorganisms Fusobacterium nucleatum (ATCC 10953) and Enterococcus faecalis (ATCC 19433) in single and bi association. The animals were sacrificed after 10 and 20 days, the periapical tissues were collected and the PCR real time dosed the cytokine expression. It was observed that the single infection with F. nucleatum induced high expression, on the 10º day, of RANKL and TNF- and this response modulation was due to IL-10. E. faecalis caused high expression of IFN- at 20º day, but this modulation in RANKL e TNF-expression was independent of IL-10 e TGF-. The bi association (F. nucleatum e E. faecalis) encouraged high expression of RANKL, TNF- e IFN-, on the 10º day, would be modulated by TGF- increased expression. It can be concluded that, in this model, gene expression of proinflammatory cytokines prevails in earlier periods of periapical changes induction with concomitant decrease in the late periods, and this is due to the regulatory cytokines IL-10 e TGF- modulation, but in a way infection-specific.